Autism spectrum problems, attention deficit, anxiety symptoms and IQ in children from 2 to 5 years - Vergara Álvarez, María Laura; Fernando Ramírez, Andrés; Navarro-Obeid, Jorge; Meza Cueto, Liliana; Vinaccia Alpi, Stefano; Mendoza Stave, Fabián José; Cárdenas Mercado, Ricardo (Gaceta Médica de Caracas, 2023)
The aim of the study was to establish the relationship between autism spectrum problems, attention deficit, anxiety symptoms, and IQ in children aged 2 to 5 years, through a quantitative correlational methodology. The sample consisted of 189 children and their parents and/ or caregivers belonging to child development centers and children’s homes in the city of Sincelejo, Colombia. The Wechsler Intelligence Scale for Preschool and elementary school children – WPPSI IV and the Child Behavior Check List – CBCL were applied. The main result was that in the Pearson correlation coefficient, anxious symptomatology and attention deficit were not related to any IQ index, while autism spectrum problems were related to the processing speed index (-0.282*).